Parasitic development in intestines and oocyst shedding patterns for infection by Eimeria uekii and Eimeria raichoi in Japanese rock ptarmigans, Lagopus muta japonica, protected by cages in the Southern Japanese Alps - 芝原, 友幸; シバハラ, トモユキ; SHIBAHARA, Tomoyuki (International Journal for Parasitology: Parasites and Wildlife, 2020)
journal article